Teacher Test Accountability. - Ludlow, Larry H. (Education Policy Analysis Archives, 2001)
Given the high stakes of teacher testing, there is no doubt that every teacher test should meet the industry guidelines set forth in the Standards for Educational and Psychological Testing. Unfortunately, however, there is no public or private business or governmental agency that serves to certify or in any other formal way declare that any teacher test does, in fact, meet the psychometric recommendations stipulated in the Standards. Consequently, there are no legislated penalties for faulty products (tests) nor are there opportunities for test takers simply to raise questions about a test and to have their questions taken seriously by an impartial panel. The purpose of this article is to highlight some of the psychometric results reported by National Evaluation Systems (NES) in their 1999 Massachusetts Educator Certification Test (MECT) Technical Report, and more specifically, to identify those technical characteristics of the MECT that are inconsistent with the Standards. A second purpose of this article is to call for the establishment of a standing test auditing organization with investigation and sanctioning power. The significance of the present analysis is twofold: a) psychometric results for the MECT are similar in nature to psychometric results presented as evidence of test development flaws in an Alabama class-action lawsuit dealing with teacher certification (an NES-designed testing system); and b) there was no impartial enforcement agency to whom complaints about the Alabama tests could be brought, other than the court, nor is there any such agency to whom complaints about the Massachusetts tests can be brought. I begin by reviewing NES's role in Allen v. Alabama State Board of Education, 81-697-N. Next I explain the purpose and interpretation of standard item analysis procedures and statistics. Finally, I present results taken directly from the 1999 MECT Technical Report and compare them to procedures, results, and consequences of procedures followed by NES in Alabama.